The Treatment of Gay and Lesbian Fiction for Young Adults in the Reviewing Media - Rothbauer, Paulette M.; McKechnie, Lynne E.F. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The treatment of potentially controversial materials is of great interest to library and information science scholars and practitioners because of the commitment of the profession to the principles of intellectual freedom and access to information. An examination of collection management activities is one way to determine if and how librarians implement these principles in their professional work.